The Sexual Assault of Intoxicated Women - Benedet, Janine (2010)
This article considers how the criminal law of sexual assault in Canada deals with cases of women who have been consuming intoxicants (e.g. alcohol and or drugs). In particular, it considers under what circumstances the doctrines of incapacity to consent and involuntariness have been applied to cases in which the complainant was impaired by alcohol or drugs. It also reflects on problems of proof in such cases. Finally, it examines whether the treatment of this class of complaints tells us anything about the law’s understanding of consent, and capacity to consent, more generally, in the context of competing social understandings of women’s use of alcohol and other drugs